A dense and smooth metallic tin based on methanesulfonic acid system and a preparation method thereof
By using a methylsulfonic acid system and specific additives during the electrolytic refining of crude tin, the tin ion electrodeposition kinetics are regulated, and the cathode tin grains are large and poor morphology is solved, and dense, flat, and high-purity metal tin electrodeposition is achieved, which is environmentally friendly and efficient.
Patent Information
- Application Number
- CN202410674416.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-28
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-05-28
AI Technical Summary
During the electrolytic refining process of existing crude tin, the metal tin grains precipitated by the cathode product due to the large exchange current are large, and dendrites or burrs are prone to appear around it, or loose and porous sponge tin is formed.
The methylsulfonic acid system is used to replace the traditional sulfuric acid-cresol/phenol sulfonic acid and fluosilicate systems, and the tin ion cathode electrodeposition kinetics are regulated by additives such as sulfodiglyethylene glycol ethylate, bone gum and α-sulfo-ω-hydroxypoly(oxy-1,2-ethylenediyl)-C12-14-alkyl ester sodium salt to achieve dense and flat metal tin electrodeposition.
Significantly improve the cathode tin deposition morphology, obtain dense and flat, with no dendrites or burrs around high-purity cathode metal tin products, and have the advantages of environmentally friendly, high current efficiency and low DC power consumption.
Smart Images

Figure CN118531447B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nonferrous metal hydrometallurgy, and in particular to a dense and smooth metallic tin based on a methanesulfonic acid system and a preparation method thereof. Background Art
[0002] Tin has excellent properties such as low melting point, soft texture, non-toxicity, corrosion resistance, and good ductility. It is widely used in electronic appliances, food processing, machinery manufacturing, automobile industry, aerospace, and energy storage. At present, the crude tin produced by tin concentrate reduction smelting is mostly removed by the fire refining process of "condensation to remove iron and arsenic - continuous crystallization / vacuum distillation to remove lead and bismuth - adding aluminum to remove antimony and arsenic" to produce refined tin products. The fire refining and impurity removal process has high production efficiency and small tin backlog, but it also has disadvantages such as low tin direct recovery rate and complicated operating procedures. The electrolytic refining process can remove most of the impurity metals in crude tin or solder in one step, and produce highly pure refined tin or refined solder. This method has a high direct recovery rate of tin, a large enrichment ratio of valuable impurity metals, and is easy to recycle and process. It is particularly suitable for processing crude tin containing bismuth and precious metals. The tin electrolytic refining system is divided into acidic electrolyte and alkaline electrolyte. Currently, industrial production is mostly carried out in sulfuric acid-cresol / phenolsulfonic acid or fluosilicic acid solution. However, these two electrolytes generally have problems such as poor stability, severe environmental pollution, and great occupational health hazards. Therefore, there is an urgent need to develop a new type of green, environmentally friendly, efficient and energy-saving crude tin electrolytic refining technology.
[0003] Methanesulfonic acid (MSA) is a biodegradable organic strong acid (pKa = -1.9) with a low saturated vapor pressure (0.13 kPa / 20°C), high saturated solubility of metal salts and high electrical conductivity. It has broad application prospects in the green extraction and electroplating of non-ferrous metals such as lead, tin, bismuth and copper. In view of this, the use of methanesulfonic acid tin acid medium to replace the traditional sulfuric acid-cresol / phenolsulfonic acid and fluorosilicic acid system can achieve green and efficient electrolytic refining and purification of crude tin. However, due to the large exchange current of tin, the metal tin grains precipitated at the cathode during the tin electrodeposition process are large, and dendrites or burrs are prone to appear around the cathode, or loose and porous sponge tin is generated. Therefore, it is very important to develop a method for regulating the cathode morphology during the tin electrodeposition process in a methanesulfonic acid system. Summary of the invention
[0004] In view of this, the present invention provides a dense and smooth metallic tin based on a methanesulfonic acid system and a preparation method thereof, so as to solve the problem that in the existing crude tin refining and purification process, the metallic tin grains precipitated from the cathode product are large due to the large exchange current, and dendrites or burrs are easily formed around them, or loose and porous sponge tin is generated.
[0005] In order to achieve the above object, the present invention adopts the following technical solution:
[0006] A method for preparing dense and smooth metallic tin based on a methanesulfonic acid system comprises the following steps:
[0007] 1) mixing stannous methanesulfonate, methanesulfonic acid and an additive to obtain a methanesulfonic acid system tin-containing electrolyte;
[0008] 2) using a crude tin plate as an anode and a tin-containing electrolyte of a methanesulfonic acid system as an electrolyte to perform electrolytic deposition to obtain dense and flat metallic tin;
[0009] The additive is one or more of thiodiglycol ethylate, bone glue and α-sulfo-ω-hydroxy poly (oxy-1,2-ethylenediyl) -C12-14-alkyl ester sodium salt.
[0010] Preferably, in the methanesulfonic acid system tin-containing electrolyte in step 1), the concentration of methanesulfonic acid is 30 to 140 g / L, and Sn 2+ The concentration is 10~60g / L.
[0011] Preferably, the concentration of the additive is 0.5-5 g / L.
[0012] Preferably, the electrolytic deposition process in step 2) further includes a cathode, and the cathode includes one of a titanium plate, a stainless steel plate and a tin sheet.
[0013] Preferably, in the process of electrolytic deposition in step 2), the temperature of electrolytic deposition is 20-80°C, the time of electrolytic deposition is 8-168h, and the current density of the cathode is 50-200A / m 2 .
[0014] Preferably, the distance between the cathode and the anode is 3 to 8 cm.
[0015] Preferably, during the electrolytic deposition process, the tin-containing electrolyte of the methanesulfonic acid system circulates in a top-in-bottom-out or bottom-in-top-out manner, and the circulation rate of the tin-containing electrolyte of the methanesulfonic acid system is 5 to 20 mL / min.
[0016] Another object of the present invention is to provide a dense and smooth metallic tin prepared by the preparation method.
[0017] It can be seen from the above technical solutions that, compared with the prior art, the present invention has the following beneficial effects:
[0018] The present invention adopts a methanesulfonic acid system to replace the traditional sulfuric acid-cresol / phenolsulfonic acid and fluorosilicic acid system for electrolytic refining and purification of crude tin, which has the advantages of being environmentally friendly, high current efficiency, and low DC power consumption. Through the screening and matching of additives, the cathode electrodeposition dynamics of tin ions is effectively regulated, the cathode tin deposition morphology is significantly improved, and a high-purity cathode metal tin product with a dense and flat surface and no dendrites or burrs around is obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0020] Figure 1 The cathode tin morphology and microstructure obtained in Example 1, wherein: Figure 1 a in the figure is the cathode tin morphology. Figure 1 The b in the figure is the cathode tin microstructure at 100 times magnification. Figure 1 Figure c is the microstructure of the cathode tin side at a magnification of 200 times;
[0021] Figure 2 The cathode tin morphology and microstructure obtained in Example 2, wherein: Figure 2 a in the figure is the cathode tin morphology. Figure 2 The b in the figure is the cathode tin microstructure at 100 times magnification. Figure 2 Figure c is the microstructure of the cathode tin side at a magnification of 200 times;
[0022] Figure 3 The cathode tin morphology and microstructure obtained in Example 3, wherein: Figure 3 a in the figure is the cathode tin morphology. Figure 3 The b in the figure is the cathode tin microstructure at 100 times magnification. Figure 3 Figure c is the microstructure of the cathode tin side at a magnification of 200 times;
[0023] Figure 4 The cathode tin morphology and microstructure obtained in Example 4, wherein: Figure 4 a in the figure is the cathode tin morphology. Figure 4 The b in the figure is the cathode tin microstructure at 100 times magnification. Figure 4 Figure c is the microstructure of the cathode tin side at a magnification of 200 times;
[0024] Figure 5 The morphology and microstructure of the cathode tin obtained in Comparative Example 1, wherein: Figure 5 a in the figure is the cathode tin morphology. Figure 5 b in the figure is the cathode tin microstructure at 100 times magnification;
[0025] Figure 6 The cathode tin morphology and microstructure obtained in Comparative Example 2, wherein: Figure 6 a in the figure is the cathode tin morphology. Figure 6b in the figure is the cathode tin microstructure at 100 times magnification;
[0026] Figure 7 The cathode tin morphology and microstructure obtained in Comparative Example 3, wherein: Figure 7 a in the figure is the cathode tin morphology. Figure 7 The b in the figure is the cathode tin microstructure at 100 times magnification. Figure 7 Figure c is the microstructure of the cathode tin side at a magnification of 200 times;
[0027] Figure 8 The cathode tin morphology and microstructure obtained in Comparative Example 4, wherein: Figure 8 a in the figure is the cathode tin morphology. Figure 8 Figure b shows the cathode tin microstructure at a magnification of 100 times. DETAILED DESCRIPTION
[0028] The present invention provides a method for preparing dense and smooth metallic tin, comprising the following steps:
[0029] 1) mixing stannous methanesulfonate, methanesulfonic acid and an additive to obtain a methanesulfonic acid system tin-containing electrolyte;
[0030] 2) using a crude tin plate as an anode and a tin-containing electrolyte of a methanesulfonic acid system as an electrolyte to perform electrolytic deposition to obtain dense and flat metallic tin;
[0031] The additive is one or more of thiodiglycol ethylate, bone glue and α-sulfo-ω-hydroxy poly (oxy-1,2-ethylenediyl) -C12-14-alkyl ester sodium salt.
[0032] In the present invention, in the methanesulfonic acid system tin-containing electrolyte described in step 1), the concentration of methanesulfonic acid is 30 to 140 g / L, specifically 40 g / L, 50 g / L, 60 g / L, 80 g / L, 100 g / L, 120 g / L; Sn 2+ The concentration of the additive is 0.5-5g / L, specifically 1g / L, 2g / L, 3g / L, 4g / L, 45g / L, 50g / L, and 55g / L; the concentration of the additive is 0.5-5g / L, specifically 1g / L, 2g / L, 3g / L, and 4g / L.
[0033] In the present invention, when the additive is gelatin, its concentration is preferably 0.5-4 g / L, specifically 1 g / L, 2 g / L, or 3 g / L.
[0034] In the present invention, the process of step 2) electrolytic deposition also includes a cathode, and the cathode includes one of a titanium plate, a stainless steel plate and a tin sheet.
[0035] In the present invention, during the electrolytic deposition process of step 2), the temperature of the electrolytic deposition is 20 to 80°C, specifically 30°C, 40°C, 50°C, 60°C, or 70°C; the time of the electrolytic deposition is 8 to 168h, specifically 10h, 20h, 24h, 30h, 36h, 48h, 50h, 60h, 72h, 80h, 100h, 120h, 140h, 150h, or 160h; the current density of the cathode is 50 to 200A / m 2 , specifically 80A / m 2 , 100A / m 2 , 120A / m 2 , 140A / m 2 , 150A / m 2 、160A / m 2 、180A / m 2 .
[0036] In the present invention, the distance between the cathode and the anode is 3 to 8 cm, specifically 4 cm, 5 cm, 6 cm, or 7 cm.
[0037] In the present invention, during the electrolytic deposition process, there may be multiple pairs of cathodes and anodes, and the distance between adjacent opposite poles is preferably 3 to 8 cm, specifically 4 cm, 5 cm, 6 cm, or 7 cm.
[0038] In the present invention, during the electrolytic deposition process, the tin-containing electrolyte of the methanesulfonic acid system is circulated in a top-in-bottom-out or bottom-in-top-out manner, and the circulation rate of the tin-containing electrolyte of the methanesulfonic acid system is 5 to 20 mL / min, specifically 6 mL / min, 8 mL / min, 10 mL / min, 12 mL / min, 15 mL / min, 16 mL / min, and 18 mL / min.
[0039] In the present invention, the same additive has different effects on the coating morphology and microscopic results of different metals. Even for the same metal, there are significant differences in the adsorption effect of the additive on the cathode surface in different metal salt electrolysis systems (such as sulfuric acid, fluosilicic acid, chloride, nitric acid, and methanesulfonic acid systems).
[0040] The invention also provides a dense and smooth metallic tin prepared by the preparation method.
[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Example 1
[0043] The tin-containing electrolyte of the methanesulfonic acid system of "stannous methanesulfonate-methanesulfonic acid-additive" is configured, wherein Sn 2+ The concentration is 30g / L, the concentration of methanesulfonic acid is 75g / L, the concentration of the additive bone glue (Hebei Huafeng Adhesive Co., Ltd.) is 2g / L, the electrolyte is circulated in a bottom-in and top-out manner (circulation rate is 10mL / min), and the electrolyte temperature is controlled at 35°C. Crude tin (Sn 97.32%) is used as the anode, titanium plate as the cathode, the inter-electrode distance is 4cm, a DC power supply is connected, and the cathode current density is set to 100A / m 2 The morphology and microstructure of the cathode tin obtained after 72 hours of electrolysis are as follows Figure 1 As shown, through Figure 1 It can be seen that the cathode metal tin has a good plate-forming effect, the metal tin grains are dense and the surface is flat. In this embodiment, the cathode current efficiency is 99.04%, the cell voltage is 0.183V, the DC energy consumption is 83.40kWhe / t Sn, and the purity of the cathode metal tin reaches 99.992%.
[0044] Example 2
[0045] The tin-containing electrolyte of the methanesulfonic acid system of "stannous methanesulfonate-methanesulfonic acid-additive" is configured, wherein Sn 2+ The concentration is 40g / L, the concentration of methanesulfonic acid is 75g / L, the concentration of the additive α-sulfo-ω-hydroxy poly (oxy-1,2-ethylenediyl) -C12-14-alkyl ester sodium salt is 1g / L, the electrolyte is circulated in a bottom-in and top-out manner (circulation rate is 15mL / min), and the electrolyte temperature is controlled at 40°C. Crude tin (Sn 97.62%) is used as the anode, stainless steel plate as the cathode, the inter-electrode distance is 4cm, a DC power supply is connected, and the cathode current density is set to 100A / m 2 The morphology and microstructure of the cathode tin obtained after 72 hours of electrolysis are as follows Figure 2 As shown, through Figure 2 It can be seen that the cathode metal tin has excellent plate forming effect, and the surface of the metal tin is dense and flat. In this embodiment, the cathode current efficiency is 99.01%, the cell voltage is 0.165V, the DC energy consumption is 75.22kWhe / t Sn, and the purity of the cathode metal tin reaches 99.991%.
[0046] Example 3
[0047] The tin-containing electrolyte of the methanesulfonic acid system of "stannous methanesulfonate-methanesulfonic acid-additive" is configured, wherein Sn 2+The concentration is 30g / L, the concentration of methanesulfonic acid is 95g / L, the concentration of the additive dithiodiglycol ethylate is 4g / L, the electrolyte is circulated in a bottom-in-top-out manner (circulation rate is 8mL / min), and the electrolyte temperature is controlled at 45°C. Crude tin (Sn 96.59%) is used as the anode, the tin starting plate is used as the cathode, the inter-polar distance is 4cm, the DC power supply is turned on, and the cathode current density is set to 150A / m 2 The morphology and microstructure of the cathode tin obtained after 24 hours of electrolysis are as follows: Figure 3 As shown, through Figure 3 It can be seen that the cathode metal tin has excellent plate-forming effect, and the surface structure of the metal tin is dense and flat. In this embodiment, the cathode current efficiency is 98.98%, the cell voltage is 0.169V, the DC energy consumption is 77.07kWhe / t Sn, and the purity of the cathode metal tin reaches 99.991%.
[0048] Example 4
[0049] The tin-containing electrolyte of the methanesulfonic acid system of "stannous methanesulfonate-methanesulfonic acid-additive" is configured, wherein Sn 2+ The concentration is 30g / L, the concentration of methanesulfonic acid is 75g / L, the concentration of the additive gelatin is 2g / L, the concentration of α-sulfo-ω-hydroxy poly (oxy-1,2-ethylenediyl) -C12-14-alkyl ester sodium salt is 0.5g / L, the electrolyte is circulated in a bottom-in and top-out manner (circulation rate is 12mL / min), and the electrolyte temperature is controlled at 35°C. With crude tin (Sn98.05%) as the anode and a stainless steel plate as the cathode, the inter-electrode distance is 4cm, a DC power supply is connected, and the cathode current density is set to 100A / m 2 The morphology and microstructure of the cathode tin obtained after 72 hours of electrolysis are as follows Figure 4 As shown, through Figure 4 It can be seen that the cathode metal tin has excellent plate-forming effect, and the metal tin surface is dense and flat. In this embodiment, the cathode current efficiency is 99.11%, the cell voltage is 0.195V, the DC energy consumption is 88.81kWhe / t Sn, and the purity of the cathode metal tin reaches 99.995%.
[0050] Comparative Example 1
[0051] Prepare a mixed electrolyte of "stannous methanesulfonate-methanesulfonic acid", in which Sn 2+ The concentration is 30g / L, the methanesulfonic acid concentration is 75g / L, no additives are added, the electrolyte is circulated in a bottom-in and top-out manner (circulation rate is 10mL / min), and the electrolyte temperature is controlled at 35°C. Crude tin (Sn 98.06%) is used as the anode, titanium plate is used as the cathode, the interpolar distance is 4cm, a DC power supply is connected, and the cathode current density is set to 100A / m 2 The morphology and microstructure of the cathode tin produced after 72 hours of electrolysis are as follows: Figure 5 As shown. Comparative Examples 1 to 4 show that when no additives are added during the electrolytic refining of crude tin, the metal tin deposited at the cathode is spongy, sparse and porous, and easily falls off from the cathode plate, making it difficult to obtain a dense and flat metal tin plate. In this comparative example 1, the cathode current efficiency is 95.35%, the cell voltage is 0.163V, the DC energy consumption is 77.16kWhe / t Sn, and the purity of the cathode metal tin reaches 99.976%. It can be seen that the current efficiency and metal tin purity of comparative example 1 are lower than those of Examples 1 to 4.
[0052] Comparative Example 2
[0053] Prepare a mixed electrolyte of "stannous methanesulfonate-methanesulfonic acid-additive", in which Sn 2+ The concentration is 30g / L, the concentration of methanesulfonic acid is 75g / L, the concentration of the additive β-naphthol is 0.25g / L, the electrolyte is circulated in a bottom-in and top-out manner (circulation rate is 10mL / min), and the electrolyte temperature is controlled at 35°C. Crude tin (Sn 98.96%) is used as the anode, titanium plate is used as the cathode, the inter-electrode distance is 4cm, a DC power supply is connected, and the cathode current density is set to 100A / m 2 The morphology and microstructure of the cathode tin produced after 72 hours of electrolysis are as follows: Figure 6 As shown. Compared with Comparative Examples 1 to 4, β-naphthol is added as an additive during the electrolytic refining of crude tin, and most of the electrodeposited metal tin falls off from the cathode plate, making it difficult to obtain a dense and flat metal tin plate. In this Comparative Example 2, the cathode current efficiency is 86.35%, the cell voltage is 0.261V, the DC energy consumption is 136.44kWhe / t Sn, and the purity of the cathode metal tin reaches 99.988%. It can be seen that the current efficiency and metal tin purity of Comparative Example 2 are lower than those of Examples 1 to 4, while the cell voltage and DC power consumption are much higher than those of Examples 1 to 4.
[0054] Comparative Example 3
[0055] Prepare a mixed electrolyte of "stannous methanesulfonate-methanesulfonic acid-additive", in which Sn 2+ The concentration is 30g / L, the concentration of methanesulfonic acid is 75g / L, the concentration of the additive gum arabic (commonly available in the market) is 1g / L, the electrolyte is circulated in a bottom-in and top-out manner (circulation rate is 10mL / min), and the electrolyte temperature is controlled at 35°C. Crude tin (Sn 97.78%) is used as the anode, the titanium plate is used as the cathode, the inter-electrode distance is 4cm, the DC power supply is turned on, and the cathode current density is set to 100A / m 2 The morphology and microstructure of the cathode tin produced after 72 hours of electrolysis are as follows: Figure 7As shown. Compared with Comparative Examples 1 and 2, the metal tin deposited at the cathode can form a plate by adding gum arabic as an additive, but compared with Examples 1 to 4, the metal tin grains are coarse, the surface of the cathode tin is uneven, there are holes in the cross section, and the density is poor. In this Comparative Example 3, the cathode current efficiency is 97.99%, the cell voltage is 0.186V, the DC energy consumption is 85.68kWhe / t Sn, and the purity of the cathode metal tin reaches 99.985%. It can be seen that its current efficiency is higher than that of Comparative Example 1, but lower than that of Examples 1 to 4; the cell voltage is lower than that of Examples 1 to 3, but higher than that of Example 4; its DC power consumption is higher than that of 1 to 3, but slightly lower than that of Example 4.
[0056] Comparative Example 4
[0057] Prepare a mixed electrolyte of "stannous methanesulfonate-methanesulfonic acid-additive", in which Sn 2+ The concentration is 30g / L, the concentration of methanesulfonic acid is 75g / L, the concentration of the additive gelatin is 2g / L, and the concentration of β-naphthol is 0.25g / L. The electrolyte is circulated in a bottom-in and top-out manner (circulation rate is 10mL / min), and the electrolyte temperature is controlled at 35°C. Crude tin (Sn 98.91%) is used as the anode, titanium plate is used as the cathode, the interpolar distance is 4cm, a DC power supply is connected, and the cathode current density is set to 100A / m 2 The morphology and microstructure of the cathode tin produced after 72 hours of electrolysis are as follows: Figure 8 As shown. Compared with Comparative Examples 1 and 2, the addition of bone glue and β-naphthol as additives, the cathode electrodeposition of metal tin plate effect is better, but dendrites appear around the metal tin and on the plate surface, and the cathode tin morphology is worse than that of Examples 1 to 4. In this Comparative Example 4, the cathode current efficiency is 97.83%, the cell voltage is 0.326V, the DC energy consumption is 150.42kWhe / t Sn, and the purity of the cathode metal tin reaches 99.983%. It can be seen that its current efficiency is higher than that of Comparative Examples 1 and 2, but lower than that of Examples 1 to 4, and the cell voltage and DC power consumption are both higher than those of Comparative Example 1 and Examples 1 to 4.
[0058] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0059] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing dense and smooth metallic tin based on a methanesulfonic acid system, characterized in that: The steps include: 1) mixing stannous methanesulfonate, methanesulfonic acid and an additive to obtain a methanesulfonic acid system tin-containing electrolyte; 2) Using a crude tin plate as an anode and a tin-containing electrolyte in a methanesulfonic acid system as an electrolyte, electrolytic deposition is performed to obtain dense and flat metallic tin; The additive is one or more of thiodiglycol ethylate, bone glue and α-sulfo-ω-hydroxy poly (oxy-1,2-ethylenediyl) -C12-14-alkyl ester sodium salt.
2. The method for preparing dense and smooth metallic tin based on a methanesulfonic acid system according to claim 1, characterized in that: In the methanesulfonic acid system tin-containing electrolyte of step 1), the concentration of methanesulfonic acid is 30-140 g / L, Sn 2+ The concentration is 10~60g / L.
3. The method for preparing a dense and smooth metallic tin based on a methanesulfonic acid system according to claim 2, characterized in that: The concentration of the additive is 0.5~5g / L.
4. The method for preparing a dense and smooth metallic tin based on a methanesulfonic acid system according to any one of claims 1 to 3, characterized in that: The electrolytic deposition process of step 2) also includes a cathode, which includes one of a titanium plate, a stainless steel plate and a tin sheet.
5. The method for preparing dense and smooth metallic tin based on a methanesulfonic acid system according to claim 4, characterized in that: Step 2) During the electrolytic deposition process, the electrolytic deposition temperature is 20-80°C, the electrolytic deposition time is 8-168h, and the cathode current density is 50-200A / m 2 .
6. The method for preparing dense and smooth metallic tin based on a methanesulfonic acid system according to claim 5, characterized in that: The distance between the cathode and the anode is 3-8 cm.
7. The method for preparing dense and smooth metallic tin based on a methanesulfonic acid system according to claim 6, characterized in that: During the electrolytic deposition process, the tin-containing electrolyte of the methanesulfonic acid system circulates in a top-in-bottom-out or bottom-in-top-out manner, and the circulation rate of the tin-containing electrolyte of the methanesulfonic acid system is 5-20 mL / min.
Citation Information
Patent Citations
Tin electrorefining electrolyte composite additive
CN108441888A